BIBLIOMETRIC MAPPING OF INFLATION DUE TO THE COVID-19 PANDEMIC IN INDONESIA USING VOSVIEWER - Putri Amelia Pasaribu; Abdul Nasser Hasibuan; Utari Evy Cahyani (JURNAL PROFIT, 2025)
This study aims to examine the impact of the COVID-19 pandemic on inflation in Indonesia. The pandemic has had a wide and profound effect on various aspects of life, including the economy. Disruptions in supply chains, changes in consumer demand patterns, and government policies are the main factors affecting inflation during the pandemic. Factory closures and social restrictions have led to shortages of goods and raw materials, thus driving up prices. Meanwhile, the increase in demand for staples and medical products has not been offset by an increase in supply, causing a spike in prices. The government's fiscal and monetary stimulus policies have also increased the money supply, potentially driving further inflation. Fluctuations in energy prices during the pandemic have also contributed to the dynamics of inflation in Indonesia. The bibliometric method is used to identify research trends, inflation and covid-19 in Indonesia as well as researcher collaboration on this topic.